ANALISIS KINERJA KOPERASI PEGAWAI NEGERI ABDI LUHUR DI MUARA BADAK - Sulimah sulimah (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2018)
Sulimah, 2017, Performance Analysis of Civil Servant Cooperative Abdi Luhur In Muara Badak (under the guidance of Mr. Levi Malisan and Mr. Rusliansyah).               The formulation of the problem is how the assessment of the Organizational Aspects, Aspects of Management and Management, Aspects of Productivity and Aspects of Benefits and Impact on the cooperative Civil Servant Abdi Luhur in Estuary Badak.               The purpose of this study is to know and analyze the assessment of the Aspects of Organization, Aspects of Management and Management, Aspects of Productivity and Aspects of Benefits and Impacts conducted by the Employee Cooperative Abdi Luhur in Estuary Badak.               The benefit of this research is for the writer of this research as an effort to deepen the science and apply the theory obtained in the course of this lecture, for the business unit / cooperative research is expected to be a reference in improving the performance of cooperatives, both in terms of management of cooperative management and financial management , for academic This research is expected to provide a useful source of thought to add insight and knowledge of this researcher, And can be used as reference material for researchers who will conduct similar research or further.               The analytical tool used in this study is the Cooperative Regulation Based on the Regulation of the State Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number: 02 / PER / M.KUKM / II / 2017 on Savings and Loans.               From the results of research conducted on the Performance of Civil Servant Cooperative Abdi Luhur in Muara Badak classified A with a score of 286.05 which means that the overall performance is quite good with based on the performance weight of the assessment Aspects Organization is equal to 84.67, Aspects of Management and Management of 62.5, Productivity Aspects of 69.44, and Aspects of Benefits and Impact of 69.44.